PEMOTRETAN GOLONGAN PENDAPATAN PEKERJA TETAP PADA PT. KURNIA ANGGUN KABUPATEN MOJOKERTO - Harjo Lukito; Mohamad Johan Efendi (OPTIMA, 2020)
This research aims to knowing to belong to a group which worker is permanent income PT. Kurnia Anggun starting from year 2010 – 2018? Population used are all workers on PT. Kurnia Anggun, while the sample is all workers is permanent in the period 2010 – 2018. Research method used in this study the survey is descriptive in using the poverty line guidelines as much as 2 US $ per day, then this research was obtained information for average income of workers remains in PT. Kurnia Anggun as follows is 1) The income of workers is far above poverty line. 2)starting at the end of the year 2016, income already above US $ 3000. 3) At the end of the year 2010 – 2015 enter the group middle income is relatively low , while at the end of the year 2016 – 2018 enter the group relatively high middle income. 4) If the beginning of the year 2018. Indonesia has business people like that in PT. Kurnia Anggun then poverty in Indonesia will disappear. What the company needs to pay attention to is always increase productivity human resources, make product innovation, increasing competitiveness and increasing added value the height of the year to yearso that the company profits not affected by increase in employee minimum wages.